HUBUNGAN ANTARA KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA KARYAWAN PRODUKSI INDUSTRI TEKSTIL - Anggraini, Sabilla; Anugerah Izzati, Umi (Penerbit Lafadz Jaya, 2025)
Human resources (HR) play an important role in the sustainability of an organization or company, especially in achieving organizational goals. This study aims to determine the relationship between organizational commitment and job satisfaction among employees in the production department at PT X. The sample in this study was all employees in the Yarn Production Department with a total of 66 respondents. This study uses a quantitative approach with a questionnaire and Pearson Product Moment correlation data analysis with the help of data processing using SPSS 27. The results of this study prove that the organizational commitment variable has a positive and significant relationship with employee job satisfaction with a correlation value of 0.549 and a significance level of 0.000 which is included in the medium category. Thus, the higher the level of employee commitment to the organization, the higher the job satisfaction felt by employees. These findings are expected to provide input for management in developing effective HR management strategies, especially in the textile industry with a rotating work system.